UNIVERSITY AND ENTREPRENEURSHIP: THE EDUCATIONAL AND STRUCTURAL APPROACHES ADOPTED IN ALGERIA, THE CASE OF SETIF 1 UNIVERSITY - Rahmani-Kelkoul, Leila; Tedjari, Abdelmalek Farouk; Rouabhi, Tarek; Rahmani, Mounir (International Online Journal of Education and Teaching, 2024)
In recent years, the Algerian university has encouraged students at the end of their cycle to create their micro- enterprise and startup to practice outside the university. They are called upon to face environmental challenges, job creation and innovation. This top-down desire enshrined in the MESRS directive falls to the university toact as a catalyst for efforts towards the socio-economic reality of its immediate and distant surroundings. This article questions the educational and structural approaches implemented to achieve these objectives. Our method is based on the collection and analysis of information collected via the structures installed and qualitative interviews with the managers of these structures and teachers from three faculties: Architecture, Economics and Science. The results showed that the university has equipped itself with support structures which work dynamically, including: an incubator, a CATI, a CDE and the BLEU. The educational aspect showed that the faculties combine between classic and semi-active method showing an insufficiency, induced by an ambivalent adaptation of the LMD system, the foundations of which are enrolled in learning the spirit of the entrepreneurship. We propose to adopt active methods with an immersion project and a bottom-up organization to achieve the targeted objectives. Keywords: University-entrepreneurship-active-method